Do cortisol and corticosterone play the same role in coping with stressors? Measuring glucocorticoid serum in free‐ranging guanacos (Lama guanicoe). Issue 10 (30th September 2013) - Ovejero, Ramiro; Novillo, Agustina; Soto‐Gamboa, Mauricio; Mosca‐Torres, Maria E.; Cuello, Pablo; Gregório, Pablo; Jahn, Graciela; Carmanchahi, Pablo
ABSTRACT Habitat can constrain and shape successful ecological and physiological strategies, thus providing the context for the evolution of life‐history traits. However, unpredictable challenges, such as storms, natural disasters, and human activities can also have great effects on stress. Glucocorticoids (GCs) are adrenal steroid hormones that play an important role in how vertebrates cope with these predictable and unpredictable environmental challenges. Although assessing GCs levels can have many applications in the study of wildlife and/or captive animals, with or without capturing individuals, it requires a species‐specific complete validation (analytical and biological) before its use. In this work, our aim was to: (a) validate a radioimmunoassay (RIA) for measuring GCs levels in L. guanicoe serum; (b) assess cortisol and corticosterone levels (if present) in serum of wild L. guanicoe individuals; and (c) compare the response to acute stressors (handling, shearing, and release). Our results successfully: (a) validated RIA for asses GCs levels in wild ungulates; (b) confirmed the presence for cortisol and corticosterone and showed that both GCs are differently affected by environmental stimuli in L. guanicoe; and (c) showed that GCs exhibit different patterns in the field and in response to acute stressors, making these camelids an interesting endocrinological model when seeking the adaptive functions of a given variation and further emphasizing the complexity of GC physiology in wild mammals. J. Exp. Zool. 319A: 539–547, 2013. © 2013 Wiley Periodicals, Inc.